2017
DOI: 10.4194/1303-2712-v17_1_20
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The antibacterial activity of Pulicaria inuloides and Pulicaria crispa essential oils was tested against Listeria monocytogenes, Escherichia coli and Staphylococcus aureus using agar disc diffusion and microtiter broth microdilution assays. PIEO, the essential oil from Pulicaria inuloides, inhibited all tested microorganisms with a minimum inhibitory concentration (MIC) of 5.7, 0.12 and 5.11 mg/ml against Listeria monocytogenes, Escherichia coli and Staphylococcus aureus respectively. PCEO, the essential oil f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The study carried out by Abdeldaiem et al [52] explored the use of rosemary, cinnamon, fennel, and cardamom EOs to prevent the proliferation of E. coli in carp flesh fingers. The authors observed that the inhibitory effect was obtained for all tested EOs, particularly in the first six days of storage at 4 • C. In the same line, Al-Hajj et al [53] evaluated the impact of Pulicaria inuloides EO on E. coli inoculated in Kachlan (Trachinotus ovatus, Linnaeus) fillets and obtained reduction of 1 log CFU/g.…”
Section: Fish and Fish Productsmentioning
confidence: 95%
“…The study carried out by Abdeldaiem et al [52] explored the use of rosemary, cinnamon, fennel, and cardamom EOs to prevent the proliferation of E. coli in carp flesh fingers. The authors observed that the inhibitory effect was obtained for all tested EOs, particularly in the first six days of storage at 4 • C. In the same line, Al-Hajj et al [53] evaluated the impact of Pulicaria inuloides EO on E. coli inoculated in Kachlan (Trachinotus ovatus, Linnaeus) fillets and obtained reduction of 1 log CFU/g.…”
Section: Fish and Fish Productsmentioning
confidence: 95%
“…The glucose-lowering benefits of oral antidiabetic drugs (OAD) have been well established. But all the drugs are not absolutely safe in a patient having CV disease [22,23]. The other two groups also showed slight statistical significance in the drug group more than the herbs, but when we followed the individual samples, the results showed a marked improvement in the herbs group more than the drug, and the reason for this is that the sample was very few compared to the sample of the drug, which was much larger.…”
Section: Discussionmentioning
confidence: 88%
“…Then two strains of E.coli and B. cereus approximately 6 log 10 CFU/g were inoculated using micropipettes on each side of fish fillet pieces to gain a final concentration of 4 log 10 CFU/g. Next, samples were dipped in solutions of ChNPs 1% and AgNPs 40.0µg/ml (w/g) water for 1 min to enable attachment (ratio of 1:3) (Al-Hajj et al, 2017), and cumin and marjoram essential oil were added to fish fillets samples appropriate volumes to the surface (two sides) of each fish fillet using micropipette so as to achieve at 500 ppm oil volume per fish flesh weight (v/w) respectively, Goulas & Kontominas (2007) (Table 1), After that, all fish fillets samples were packaged in a foam plates, wrapped with polyethylene and stored at 4±1C up to 12 days. The samples were taken for analysis every 3 days periodically.…”
Section: Methodsmentioning
confidence: 99%